Community Tradition about Center Rope Care Using Powder and Oil For New-Born Babies - Sulfianti Sulfianti; Ismawati Ismawati (Journal La Medihealtico, 2021)
Newborn care is a process of deeds, ways of caring for and nurturing. The most important care of the umbilical cord is to make sure the umbilical cord and the area around it is always clean and dry and avoid infection. Always wash your hands using clean water and soap, before cleaning the umbilical cord. This study aims to analyze in depth the care of the umbilical cord using powder and oil in newborns in the Ajangale Community Health Center, Bone Regency. This type of research used in this research is qualitative research. Qualitative research is a study aimed at describing and analyzing phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts of people individually or in groups. This research was conducted in the work area of ​​Arenaale Public Health Center, Bone District. The number of research subjects was 10 people. The results showed that the people of Ajangale Subdistrict in the care of newborns, especially the tradition of umbilical cord care using powder, were still practiced by several people who were believed to be able to accelerate dryness and detachment of the umbilical cord. There are still people in Ajangale who perform umbilical cord care using powder and oil which are considered to be able to accelerate the dryness of the umbilical cord and quickly release it.